THE INFLUENCE OF MILK-CLOTTING ENZYMES ON THE FUNCTIONAL PROPERTIES OF PIZZA-CHEESES - D. S. Myagkonosov; V. A. Mordvinova; I. N. Delitskaya; D. V. Abramov; E. G. Ovchinnikova (Пищевые системы)
The effect of the type and dose of milk-clotting enzymes (Chy-max® M based on recombinant camel chymosin, Fromase® TL based on Rhizomucor miehei protease) on the physicochemical, functional properties and shelf life of pizza-cheeses was studied. When using a low dose of milk-clotting enzymes (MCE) for milk coagulation (250–1100 IMCU per 100 kg of milk), cheeses were obtained with an increased moisture content (55–57%), excessive acidity (pH 4.8–4.9) and texture defects (incoherent, crumbly, with separation of free moisture). This is due to the formation of a weak curd, which releases moisture poorly during processing. The use of an increased dose of MCE makes it possible to obtain a denser curd, better releasing moisture. Cheese produced with a high dose of milk-clotting enzymes (2000–2800 IMCU per 100 kg of milk) had a lower moisture content (52–53%) and lower acidity (pH 5.0–5.1). The protein matrix is more hydrated in these cheeses, which ensures its better water holding capacity and a more homogeneous and cohesive texture. The use of an increased dose of MCE with a high total proteolytic activity (Fromase) gives undesirable consequences in the form of accelerated proteolysis of cheese mass proteins, rapid loss of functional properties of the cheese, and a decrease in the shelf life of cheese (less than 60 days). Cheese production using an increased dose of MCE with a low level of total proteolytic activity (Chy-max M) allows achieving a low level of proteolysis during cheese ripening and increasing its shelf life.